The Potential of Aloe Vera as a Herbal Feed Additive for Livestock- A Review - Saini, Ravinder; Chhikara, Suresh Kumar; Sahu, Subhasish; Yadav, Dipin Chander (International Journal of Bio-resource and Stress Management, 2022)
Aloe barbadensis (Aloe vera) is one of the most important medicinal succulent and perennial plant which belongs to Liliaceae family and its leaves have several medicinal and therapeutic properties. Aloe vera leaves contain more than 200 nutrients and plant bioactive compounds especially anthraquinones, anthrones, chomones, flavonoids, tannins, polysaccharides and saponins. These active principles posses growth stimulatory, immunomodulatory, antiinflammatory, antiviral, antifungal, wound healing, antidiabetic and antioxidant properties. The major mortality in livestock is recorded due to enteric infections. To overcome these implications, the excessive or repetitive prophylactic use of drugs against problems is not only costly but also renders animals and human body prone to development of drug resistance; it prompted researchers to look for alternative of drugs to control the disease. Phytogenic feed additives are a new class of feed additives for poultry and livestock industry that have gained attention as a result of their beneficial properties like antibacterial, antifungal, anti-inflammatory and growth promoters. Realizing this, a number of phytogenic feed additives (PFA) have been identified for their use as feed additive including Aloe vera which in turn may improve the performance of livestock. Presently, Animal nutritionists have carried out lot of studies to harvest the potential of Aloe vera as herbal feed additive. In this review article, major studies have been included which were carried out by various researchers to find out the effect of Aloe vera as herbal feed additive on growth, health and economic parameters of livestock.